INISIASI PROGRAM PASIR PUTIH MANDIRI PUPUK BOKASHI (PUTRI KASIH) DI DESA PASIR PUTIH SITUBONDO - Wulanjari, Distiana; Ardi Nugraha, Hilman; Sahira Febriany, Natazya; Afifah, Nuha; Sari, Virda; Natasya Burah, Maria Alexandra; Nurrachman, Akbar Husaini (Program Studi Agronomi Fakultas Pertanian Universitas Jember, 2024)
The Community Service activities have been carried out take the theme of Environmental Care Village and Renewable Energy. PUTRI KASIH or Pasir Putih Mandiri Bokashi Fertilizer Production is the main program carried out in KKN activities by the 178 groups in the form of socialization activities, training, trials on seeds, and monitoring of the manufacturing process to evaluation. All activities were implemented in 2 hamlets, with the main target being the Association of Farmer Groups (Gapoktan). The results of the activities showed a positive response from the community in the form of participatory values and enthusiasm in following a series of agendas that had been designed. The series of activities in the PUTRI KASIH program produced output such as (1) The knowledge quality improvement of the community regarding the use of animal dung, such as cows, as an alternative fertilizer, (2) Improvement of the quality of the village as an independent village by making organic fertilizer or bokashi from animal waste, (3) Organic fertilizer has been made and packaged by creating its branding/label and leaflets to guide the community in making fertilizer. On the other hand, there were participatory and disciplinary values of KKN students. This program also became an assessment program to improve the quality of their respective performance, as evidenced by the results of the products produced by the society.